1982
DOI: 10.1136/jcp.35.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal gammopathies in the adult population of Finistère, France.

Abstract: SUMMARY Three hundred and thirty-four monoclonal gammopathies were detected in the sera of 30 279 adults from Finistere.Monoclonal gammopathies (MG) are more common in Finistere than in Paris and their distribution is not homogeneous. IgG paraproteins are particularly common in the northeast of Finistere whereas IgM paraproteins are more common in the southwest. Family studies and the high degree of inbreeding would support the hypothesis that there is a genetic predisposition to develop MG but the occurrence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
90
7
3

Year Published

1984
1984
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(115 citation statements)
references
References 18 publications
15
90
7
3
Order By: Relevance
“…For many years, it was considered that the prevalence of MGUS was 1 and 3 % in persons older than 50 and 70 years, respectively. [10][11][12][13][14] However, in a recent study performed on residents of Olmsted County (MN, USA), the prevalence of MGUS has been found to be even higher than what was previously reported (that is, 3.2 and 5.3% in persons older than 50 and 70 years, respectively). The median age at diagnosis is around 70 years and less than 2% patients with MGUS are under the age of 40 years.…”
Section: Epidemiologymentioning
confidence: 39%
“…For many years, it was considered that the prevalence of MGUS was 1 and 3 % in persons older than 50 and 70 years, respectively. [10][11][12][13][14] However, in a recent study performed on residents of Olmsted County (MN, USA), the prevalence of MGUS has been found to be even higher than what was previously reported (that is, 3.2 and 5.3% in persons older than 50 and 70 years, respectively). The median age at diagnosis is around 70 years and less than 2% patients with MGUS are under the age of 40 years.…”
Section: Epidemiologymentioning
confidence: 39%
“…However, a higher risk of MGUS has been demonstrated in farmers, industry workers, and those with a history of occupational or environmental exposure to toxins. 39 Occupational exposure to asbestos, aromatic hydrocarbons, fertilizers, mineral oils and petroleum, paints and related products, pesticides, and radiation is also significantly associated with an increased risk of MGUS. 40,41 A link also exists between heavy tobacco smoking and various hematologic conditions, including MGUS.…”
Section: Sexmentioning
confidence: 99%
“…On average, the prevalence of MGUS is 1.5 times higher in men than in women. 13,15,16,18,20,21,39,49 Differences in age composition of cohorts between studies influence sex-specific prevalence estimates because the condition is very rare in those younger than 40 years. For example, the population-based study by Axelsson et al 16 reported a prevalence of 1.1% in men and 0.8% in women aged 25 to 99 years.…”
Section: Sexmentioning
confidence: 99%
“…On the basis of a limited number of reports, IgM MGUS appears to be substantially less frequent in Eastern Europe (38), Greece (39), and Israel (29) and intermediate in southern European countries such as Spain (41) and Italy (37). Geographical variation also appears within populations of western European descent (42,44,47). In particular, a study of blood donors in France demonstrated remarkable variation by region, ranging from 0% (in a group of mostly urban dwellers in Paris) to 33% (in residents of an agricultural district in western France) (44).…”
Section: S93mentioning
confidence: 99%
“…Others evaluate defined population of interest, such as atomic bomb survivors (27) or elderly residents in a retirement home (31,34). A few represent unselected registry-based (36) or geographically defined (16,26,43,47,48) populations.…”
Section: S93mentioning
confidence: 99%